Empatia, neuroscienze e dolore - Empathy, neurosciences and pain - Marco Lacerenza; Chiara Cerami (Publiediting, 2010)
The comprehension of other peoples' mental condition and the identifi cation with their emotional experience are not only the basis of social life but also the foundation of the relationship between the health worker and and ill patient. Empathy pushes people to join up together and helps them in establishing emotional and social relationships with others. Although the value of empathy was already recognised in the 1850's, it has often been considered as an epiphenomenon only, without any scientific ground, rather than an actual cognitive function. Scientists have investigated empathic capacity for a long time but, just recently, Social Neuroscience has shed light on this subject, showing its importance not only for the individual but above all for the whole community.